Poetry Translation Of “Kamus Kecil” By Joko Pinurbo From English-Indonesian: Semantic Analysis of Literary Works - Gheta, Hermawan (ELATICS JOURNAL, 2024)
Poetry is a literary work that often invites readers to think deeply first to find the true meaning delivered. This research explored the meaning of poetry which was transferred through the translation process from Indonesian to English seen from the semantic meaning in both source and target languages. The aim of this research was to analyze how the semantic meaning in poetry could be maintained and adjusted in the translation process. Data were obtained from the poem "Little Dictionary" by Joko Pinurbo and its translation in English. Descriptive qualitative research was implemented with an emphasis on semantic analysis viewed from the shifts in meaning, connotation and cultural nuances in both the source language and the target language. The research results show that translating poetries in “Little Dictionary” required a balance between the accuracy of the meaning and the aesthetic beauty of the literary language. This research contributes to further understanding of the challenges and strategies in literary translation, especially poetry, as well as their relevance in introducing Indonesian literary works to the international realm.